University campus and Prehispanic heritage. Drawing the heritage imaginaries of the UNI huacas - Ausejo Calmet, Luciana (2019)
The issue of pre-Hispanic heritage is related to the city and its physical and historical relations, however,the social implications are not openly manifested in scientific texts. The objective of this articleis to understand the subjects' view of the pre-Hispanic heritage of the National Engineering Universitycampus. This research focuses not only on their own experiences, but also on reflections onother university campuses that have prehispanic heritage in Lima, and what is the impact of this ontheir social, cultural and educational dynamics, and thus raise the possibility of including the heritageas a key piece in the new vision of university and learning.